Library Crime and Security: An International Perspective, 1st edition - Lincoln, Carol Zall (Routledge, 2020)
This book, first published in 1987, focuses on the patterns of library crime and disruption in Great Britain, Canada, and the United States. In addition to important data on these problems, there is extensive information on the characteristics of the institutions and the communities in which they are found. The impact of crime on the institution and the individual is examined. The authors present vital insights into the design of crime control programs in libraries of varying sizes that have or anticipate problems with crime such as book theft, vandalism, problem patrons, and attacks against staff. Major issues in the measurement, incidence, and consequences of crime are included, as well as relevant materials from the fields of library science, management, criminology, victimology, and security. An extensive security checklist is included that can serve as a guide for making the library a safer and more secure setting for staff, patrons, and contents.